Werner Leibbrand, Annemarie Wettley and controversies on "euthanasia" the background of medico-historical and ethical debates in the Post World War II era - Wiesinger, Christine; Frewer, Andreas (Medizinhistorisches Journal, 2014)
Psychiatrists and medical historians Werner Leibbrand (1896 - 1974) and Annemarie Wettley (1913 - 1996) are amongst the most striking figures in the field of history of medicine. Leibbrand was appointed director of the "Heil- und Pflegeanstalt" in Erlangen shortly after the war. Fuelled by his own experiences of suppression and persecution during the Nazi era he promised to unearth the crimes and atrocities which had happened under watch of the Nazi regime. He was joined by Annemarie Wettley, who worked as a physician at the hospital and had developed an increasing interest in the history of medicine. In 1946 they published "Um die Menschenrechte der Geisteskranken" ("Human Rights of the Mentally Ill") about the "euthanasia" campaign of the Nazi regime. Although a number of substantial works followed, Leibbrand and Wettley failed to inform in more depth on crimes and atrocities, for instance killings of patients and forced malnutrition. Doubts and charges against Wettley regarding her role in dietary programmes at the Erlangen hospital and against Leibbrand regarding special expert's reports–both had a short-term arrest warrant–might have contributed to stagnation in their efforts. In 1953 Leibbrand accepted the offer of a chair at the University in Munich, Wettley followed and habilitated in history of medicine; in the year 1962 they married. Contacts and exchange amongst medico-historical experts shed light on developments during the post-war era; still, a critical and fundamental review of the crimes within the medical system of the Nazi regime did not take place during this time.
EVALuna2:5660